Analysis of the domestic pharmaceutical market drugs for the treatment of urolithiasis - V. L. Shevina; N. V. Khokhlenkova; T. G. Yarnykh (Zaporozhye State Medical University, 2014)
Urolithiasis is a metabolic disease caused by various endogenous and (or) exogenous factors, often is hereditary and is defined by the stone presence in the urinary system. Antibacterial therapies, herbal medicine, dietary restrictions, mineral water are used in the complex treatment of patients with urolithiasis after removal of concrement by different methods. The search for new and improvement of already known methods of treatment of urolithiasis remains relevant to date. Along with the use of synthetic drugs the use of herbal remedies that have diuretic, antispasmodic, bacteriostatic and many other effects is appropriate. An extremely valuable feature of herbal products is their ability to enhance excretion of urea and other nitrogenous waste products of metabolism, which is especially important in cases of severe renal failure of different aetiology. Note, however, that the range of herbal medicines used for the treatment of urolithiasis with symptoms of azotaemia is rather limited. The aim of our study was to investigate the range of medicines used to treat urolithiasis presented in the domestic pharmaceutical market by different countries, as well as to determine whether the Ukrainian medicines are available in the domestic market. Materials and Methods The analysis of products' range was performed according to the State Register of Medicines of Ukraine and АТС classification system. The object of the study was the medicinal products, which are used for treatment of urolithiasis. Results The products were analysed according to three АТС groups: products that inhibit uric acid synthesis; other urologicals; solvents of urinary concrement. The study has shown that 21 products are registered in Ukraine (June 2014). It has been established that the market is distributed almost equally between domestic and foreign manufacturers i.e. 8 foreign and 7 domestic manufacturers are present in the pharmaceutical market. The next stage of research was to identify the value of drugs. In the market of Ukraine manufacturers mainly offer the medicines of natural origin, which is 66.66%. For further study of this segment, the products were subject to analysis regarding their pharmaceutical form. The studies have revealed that in the pharmaceutical market of Ukraine the drugs are presented in the following pharmaceutical forms: tablets - 32%, capsules - 11 %, syrups - 16 %, drops - 17 %, gel, powders, granules and teas - 6 % of each. Thus, the most common dosage form is tablets. It is worth mentioning that to date, in the pharmaceutical market of Ukraine the main portfolio of the medicinal products in tablets is compiled by the medicinal products of foreign origin. The share of registered medicinal products in tablets manufactured by Ukrainian manufacturers versus imported medicines is 33.33 % to 66.66 %. However, only one domestic manufacturer present in the market produces the tablets of plant crude: knotweed extract powder, St. John's wort extract powder, horsetail extract dry, avisan. Conclusions The study of the market of medicinal products used for treatment of urolithiasis approved in Ukraine has been performed. It has been established that the pharmaceutical market of Ukraine presents 21 trade names of drugs used to treat urolithiasis. Preparations are analyzed depending on the origin and content of active components, presentation, type of dosage form. Based on the marketing analysis, it has been established that regardless of the general quantity of medicines of plant origin, in the study group the share of herbal medicines in tablets is insignificant (1 manufacturer). The feasibility of study regarding the development of products of plant origin in tablets for treatment of urolithiasis has been confirmed.